2011
DOI: 10.1111/j.1475-1305.2010.00765.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoothing Measured Displacements and Computing Strains Utilising Finite Element Method

Abstract: A method for smoothing measured displacements and computing strains utilising finite element and least-squares methods is proposed. Nodal displacement values of a finite element model are determined by fitting the interpolation functions of elements to measured displacement values using the method of least-squares. The displacements in the region where the measurement values are not obtained or unreliable are determined by solving finite element equations. Then, strains are obtained using a displacement-strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…In the context of the J-integral evaluation, data are also missing near to the traction-free surfaces of the crack. One solution to this problem has been proposed by Molteno [50] who used linear interpolation in the crack tip and crack flank region, whilst Yoneyama [51] proposed a finite element method to smooth the measured DIC displacement field using the measured boundary conditions; smoothing algorithms that are not based on FE approaches have also been used [52]. Full-field measurements of the boundary conditions as inputs to FE have previously been used to calculate strain and stress fields; for instance, one of the first applications was in 1990 when Morton et al [53,54] uses FE to extract stresses from moiré interferometry measurements of the crack displacement field, and more recently, Caimmi [55] made use of FE to compute the stresses from DIC-measured strains, using a hyperplastic material model.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the J-integral evaluation, data are also missing near to the traction-free surfaces of the crack. One solution to this problem has been proposed by Molteno [50] who used linear interpolation in the crack tip and crack flank region, whilst Yoneyama [51] proposed a finite element method to smooth the measured DIC displacement field using the measured boundary conditions; smoothing algorithms that are not based on FE approaches have also been used [52]. Full-field measurements of the boundary conditions as inputs to FE have previously been used to calculate strain and stress fields; for instance, one of the first applications was in 1990 when Morton et al [53,54] uses FE to extract stresses from moiré interferometry measurements of the crack displacement field, and more recently, Caimmi [55] made use of FE to compute the stresses from DIC-measured strains, using a hyperplastic material model.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the NR method is used in DIC to obtain displacement gradients, but this method cannot adequately estimate the strain field due to the unavoidable influences of different types of noises (Quan et al, 2008). In this sense, it has been found that Savitzy-Golay (SG) filter is able to improve the strain fields compared to NR process (Tang et al, 2010;Quan et al, 2008;Yoneyama, 2011;Begonia et al, 2017). For this reason, an approach proposed by Tang et al (2010) based a 2-D SG filter differentiator is used in this work in order to obtain the strain field.…”
Section: Skin Strain Computationmentioning
confidence: 99%
“…5(b)), which indicates a discernible scattering of calculated y u among the POIs. To obtain precise strain field from DIC results, further processing is required [36][37][38][39].…”
Section: (B)mentioning
confidence: 99%